Off the record - Garrett, Camryn (New York : Alfred A. Knopf, 2021)
"A teen journalist uncovers the #metoo scandal of the decade: a bigshot Hollywood director is taking advantage of cast members"--Provided by the publisher.
Junior Library Guild
Ages 15-17.
Grades 10-12.
HL610
A Junior Library Guild selection
Keywords: African Americans -- Juvenile fiction; Journalism -- Juvenile fiction; Sexual abuse -- Juvenile fiction; African Americans -- Fiction; Journalism -- Fiction; Sexual abuse -- Fiction; Youths' writings; African Americans -- Fiction; Journalism -- Fiction; Sex crimes -- Fiction